2017
DOI: 10.1103/physreve.96.033203
|View full text |Cite
|
Sign up to set email alerts
|

Capacitively coupled rf discharge with a large amount of microparticles: Spatiotemporal emission pattern and microparticle arrangement

Abstract: The effect of micron-sized particles on a low-pressure capacitively-coupled rf discharge is studied both experimentally and using numerical simulations. In the laboratory experiments, microparticle clouds occupying a considerable fraction of the discharge volume are supported against gravity with the help of the thermophoretic force. The spatiotemporally resolved optical emission measurements are performed with different arrangements of microparticles. The numerical simulations are carried out on the basis of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(65 citation statements)
references
References 57 publications
10
55
0
Order By: Relevance
“…Experimental data of the electrostatic potential or densities of electron and ions in fine particle plasma, especially in fine particle clouds, are not easy to access directly and are usually obtained by combinations of some experimental observations and simulations. The tendency of enhanced charge neutrality has been shown in [14][15][16][17] and the parallel behavior of the ion charge density and particle charge density shown in [10] is observable in figure 4 in [18].…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Experimental data of the electrostatic potential or densities of electron and ions in fine particle plasma, especially in fine particle clouds, are not easy to access directly and are usually obtained by combinations of some experimental observations and simulations. The tendency of enhanced charge neutrality has been shown in [14][15][16][17] and the parallel behavior of the ion charge density and particle charge density shown in [10] is observable in figure 4 in [18].…”
Section: Introductionmentioning
confidence: 75%
“…We have shown that the model works as an approximation by comparing its prediction with numerically obtained results. Though there seem to be no experimental data of electron, ion and particle densities or the potential under gravity for more or less direct comparison, we expect they may become available, for example, similarly to those in [18]. where variables without arguments denote those at y.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of calculation based on formulas (15), (18)- (20) for the discharge in argon are shown in Figs. 2-4.…”
Section: Ionization Equation Of State For the Dust Cloudmentioning
confidence: 99%